2012
DOI: 10.1016/j.tins.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Nerve dependence in tissue, organ, and appendage regeneration

Abstract: Many regeneration contexts require the presence of regenerating nerves as a transient component of the progenitor cell niche. Here we review nerve involvement in regeneration of various structures in vertebrates and invertebrates. Nerves are also implicated as persistent determinants in the niche of certain stem cells in mammals, as well as in Drosophila. We consider our present understanding of the cellular and molecular mechanisms underlying nerve dependence, including evidence of critical interactions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
226
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(232 citation statements)
references
References 68 publications
6
226
0
Order By: Relevance
“…A FGF8-SHH circuit encoding positional information was identified in the regenerating salamander limb (13). The requirement of PNS innervation for regeneration competence of appendages has been well documented in fish and salamanders (1,9,(14)(15)(16)(17), while denervation experiments in a rodent model found that regeneration in the absence of nerves results in an abbreviated regenerate with abnormal patterning (1). Yet, as no evidence of a specific cellular and molecular contribution of the PNS to the mammalian regenerative process had previously been reported, the experiments performed by Johnston et al demonstrate the necessity of Schwann cells in multiple mammalian models of regeneration, including dermal wound healing and digit tip regeneration, and are thus of particular relevance to tissue engineering and regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…A FGF8-SHH circuit encoding positional information was identified in the regenerating salamander limb (13). The requirement of PNS innervation for regeneration competence of appendages has been well documented in fish and salamanders (1,9,(14)(15)(16)(17), while denervation experiments in a rodent model found that regeneration in the absence of nerves results in an abbreviated regenerate with abnormal patterning (1). Yet, as no evidence of a specific cellular and molecular contribution of the PNS to the mammalian regenerative process had previously been reported, the experiments performed by Johnston et al demonstrate the necessity of Schwann cells in multiple mammalian models of regeneration, including dermal wound healing and digit tip regeneration, and are thus of particular relevance to tissue engineering and regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Urodeles regenerate entire limbs by proliferation of fate-restricted stem and progenitor cells and form a blastema, the collection of cells at the interface of stump and wound epidermis, in a process mediated by nerve-derived factors (6)(7)(8)(9)(10). In Urodeles, surgical denervation before amputation results in the inhibition of blastema formation, and ultimately results in regeneration failure.…”
mentioning
confidence: 99%
“…Recent studies have shown that purinergic signalling is a key element in cell proliferation [32][33][34][35] and in nerve physiology [36][37][38]. Finally, ATP is an essential molecule in the communication between neuron and glia [39], an essential function in systems in which regeneration is nerve-dependent [40,14].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…It is well known that innervation plays a crucial role in blastema formation and growth [12,13] (for review, see [48,1,14]). As adenosine is a key regulator of neuron physiology [49,50], we analysed the impact of apoptosis inhibition and adenosine treatment on sensory neuron regrowth after amputation (Fig.…”
Section: Purinergic Pathway Downstream Of Apoptotic Cells Is Essentiamentioning
confidence: 99%
See 1 more Smart Citation